2019
DOI: 10.1007/978-3-030-28464-0_41
|View full text |Cite
|
Sign up to set email alerts
|

Servitization of Biomass Processing for a Virtual Biorefinery: Application to the Lignocellulosic Biomass in a French Local Territory

Abstract: Processing biomass requires four major steps (pretreatment, fermentation, separation and purification) achieved by dedicated plants called biorefineries. These highly specialized structures cannot cope with the high variability of the whole biomass supply chain. Thus, providing agility to biorefineries is a key challenge to foster biomass processing. The goal is to design a virtual biorefinery as a collective network supported by the servitization of unit operations and the reuse of existing devices. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…They contribute to the organizational agility. Given the nature of Industry 4.0 ecosystem, companies rely more upon the data-driven approach of decision-making [107]. The big data supported by analytics brings accuracy in the predictive models of demand and supply [108].…”
Section: Big Data and Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…They contribute to the organizational agility. Given the nature of Industry 4.0 ecosystem, companies rely more upon the data-driven approach of decision-making [107]. The big data supported by analytics brings accuracy in the predictive models of demand and supply [108].…”
Section: Big Data and Analyticsmentioning
confidence: 99%
“…Moreover, it is suggested that the change induced by adopting Industry 4.0 technologies is not ordinary but rather a radical change in culture, structure and operations of organizations [139,[141][142][143]. Thus, only organizations which develop a nascent capability of agility will be better off by adopting Industry 4.0 technologies [107,[144][145][146]. Therefore, it can be concluded that organizations that have agility will be able to adopt Industry 4.0 technologies, and once adopted, the capability of agility will become highly dynamic [144,147,148].…”
Section: Aspect Of Agility In Industry 40mentioning
confidence: 99%
“…impure feedstock) to design a novel production line built through the reuse of existing devices (unit operations, energy supplieers, logistical units). A case study is presented in Houngbe et al (2019).…”
Section: Distributed Production and The Management Of Informationmentioning
confidence: 99%